Reliability and Concurrent Validity of a Markerless, Single Camera, Portable 3D Motion Capture System for Assessment of Glenohumeral Mobility. - Ofra Pottorf; Daniel Vapne; Jamie Ghigiarelli; Kaitlyn Haase (North American Sports Medicine Institute, 2023)
# Introduction Recent technological advancements have enabled medical, sport, and fitness professionals to utilize digital tools that assist with conducting movement examinations and screenings. One such advancement has been the implementation of a single camera, markerless, and portable 3D motion capture system designed to obtain ROM measurements for multiple body parts simultaneously. However, the reliability and validity of a markerless 3D motion capture system that uses a single camera has not been established. # Purpose The purpose of this study was to investigate the reliability and concurrent validity of this 3D motion capture system compared to a goniometer in assessing ROM of the glenohumeral joint. # Study Design Quasi-experimental reliability, convenience sampling. # Methods/materials Forty healthy volunteers (mean ± SD, age 27.4 ± 12.4 years, height 173.4 ± 11.1 cm, weight 72.1 ± 16.2 kg) participated in this study. Intrarater reliability was analyzed by ICC~(2,k)~ with a 95% CI using two repeated trials for each shoulder movement (flexion, abduction, external rotation, internal rotation) that were recorded simultaneously via two methods: a standard goniometer and a 3D motion capture system. Concurrent validity was analyzed using Pearson Correlation Coefficient (*r*). # Results The intrarater reliability between the two instruments for glenohumeral motions yielded an overall ICC of 0.82 (95% CI: 0.74-0.88) indicating good reliability for both instruments. The 3D motion capture system demonstrated strong correlations with goniometry for shoulder flexion (r = 0.67), abduction (r = 0.63), and external rotation (r = 0.76), and very strong correlation for shoulder internal rotation (r = 0.84). # Conclusion Results from this study indicated that a markerless, single camera, portable 3D motion capture system can be a reliable and valid tool to assess glenohumeral joint ROM in comparison to a standard goniometer. # Level of Evidence 3